Turtle Nest-Site Choice, Anthropogenic Challenges, and Evolutionary Potential for Adaptation - Topping, Nicholas E.; Valenzuela, Nicole (Frontiers in Ecology and Evolution, 2021)
Oviparous animals, such as turtles, lay eggs whose success or demise depends on environmental conditions that influence offspring phenotype (morphology, physiology, and in many reptiles, also sex determination), growth, and survival, while in the nest and post-hatching. Consequently, because turtles display little parental care, maternal provisioning of the eggs and female nesting behavior are under strong selection. But the consequences of when and where nests are laid are affected by anthropogenic habitat disturbances that alter suitable nesting areas, expose eggs to contaminants in the wild, and modify the thermal and hydric environment experienced by developing embryos, thus impacting hatchling survival and the sexual fate of taxa with temperature-dependent sex determination (TSD) and genotypic sex determination (GSD). Indeed, global and local environmental change influences air, water, and soil temperature and moisture, which impact basking behavior, egg development, and conditions within the nest, potentially rendering current nesting strategies maladaptive as offspring mortality increases and TSD sex ratios become drastically skewed. Endocrine disruptors can sex reverse TSD and GSD embryos alike. Adapting to these challenges depends on genetic variation, and little to no heritability has been detected for nest-site behavior. However, modest heritability in threshold temperature (above and below which females or males develop in TSD taxa, respectively) exists in the wild, as well as interpopulation differences in the reaction norm of sex ratio to temperature, and potentially also in the expression of gene regulators of sexual development. If this variation reflects additive genetic components, some adaptation might be expected, provided that the pace of environmental change does not exceed the rate of evolution. Research remains urgent to fill current gaps in our understanding of the ecology and evolution of nest-site choice and its adaptive potential, integrating across multiple levels of organization.